PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA GURU PADA SMP NEGERI 2 BANGKO BAGANSIAPI-API - Dzikra, Faira Medina (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This research was conducted at SMP Negri 2 Bangko Bagansiapi-Api. This study was conducted seminar proposal. The population of this research is the Employee in the year 2021 amounted to 42 people. Because the population is a little bit then all the population on to make samples or called a total sampling technique. So the sample in this study was 42 Teachers of SMP Negri 2 Bangko Bagansiapi-Api. Data analysis in this research uses descriptive quantitative method. Based on the results of data processing obtained that hypothesis testing with t-test there is a tcount of 5,208 means tcount = 5,208 > ttable = 2,02108 which means there is significant influence between the variables of the environment on the performance of teachers of SMP Negri 2 Bangko Bagansiapi-Api. And based on the linear regression equation there is significant influence between the variables of the environment on the performance of teachers of SMP Negri 2 Bangko Bagansiapi-Api. that is indicated by the value of the determinant coefficient (R Square) of 0,404 this means that the influence of the environment on the performance of teachers is by 40.4 % while the remaining amount (100 % to 40.4 = 59,6 %) is influenced by other variables outside of this environment variable